tPA Point Mutation at Autolysis Loop Enhances Resistance to PAI-1 Inhibition and Catalytic Activity - Peng, Shuangzhou; Xue, Guangpu; Chen, Shanli; Chen, Zhuo; Yuan, Cai; Li, Jinyu; Huang, Mingdong (Thrombosis and Haemostasis, 2019)
Recombinant tissue-type plasminogen activator (r-tPA) was approved by U.S. Food and Drug Administration as a thrombolytic drug. However, a high dose of r-tPA (up to 100 mg/person) is typically used in clinical applications. Such high dosage leads to severe side effects including haemorrhage and neurotoxicity, which can be fatal. To improve the proteolytic properties of tPA to enhance thrombolytic therapy, we designed a series of mutants in tPA serine protease domain (tPA-SPD) based on the crystal structure of tPA-SPD:plasminogen activators inhibitor-1 (PAI-1) complex that we determined recently. We found that the A146Y substitution in tPA-SPD(A146Y) enhanced resistance to PAI-1 inactivation by 30-fold compared with original tPA-SPD. Interestingly, the tPA-SPD(A146Y) variant showed fivefold higher activation for plasminogen compared with tPA-SPD. The variant also demonstrated thrombolytic activity stronger than tPA-SPD in a clot lysis assay. In vivo, we showed tPA-SPD(A146Y) possessed higher thrombolytic efficacy in a pulmonary embolism model compared with original tPA-SPD. Furthermore, a mouse tail bleeding assay showed that tPA-SPD(A146Y) did not increase bleeding risk compared with clinical drug r-tPA. Together, our findings reveal novel functions of A146Y variant, which not only increases the catalytic efficiency of the enzyme, but also enhances resistance to PAI-1 inhibition, and demonstrating that tPA-SPD (A146Y) variant is a much improved agent for thrombolytic therapy.
Keywords: tissue-type plasminogen activator; PAI-1 resistance; thrombolysis; stroke; bioengineering